Gestão estratégica e governança organizacional: o caso da secretaria das finanças de Fortaleza - Siqueira, Liane Carneiro de (2023)
This thesis is a study on strategic management and organizational governance from the perspective between these two administration constructs, when inserted in the Municipal Secretary of Finance (Sefin) context, an integral part of the direct administration of the Fortaleza City Hall, state of Ceará. Thus, the strategy used in the research included a specialized literature review, focusing the study on the approaches and recommendations presented in the Basic Referential of Organizational Governance for public organizations and other entities under the jurisdiction of the Federal Court of Accounts, thus deepening the understanding of the phenomenon to be analyzed. This work is characterized as a descriptive and field research, with data collection instruments that combine a questionnaire with the use of the Likert scale and a semi-structured interview form. The research design implied the execution of methodological procedures that covered a qualitative and quantitative approach to the problem, from the perspective of the key actors of Sefin in its natural environment. The results show that there is an effective strategic management, with the activities inherent to the processes of formulation and implementation of strategies consolidated in the institution. However, organizational governance practices require improvement, as well as the institution's current management and governance model, aiming at a good interrelationship between the two studied constructs. A relevant point of the results is the continuous effort of the current management in the search for an effective strategic management at Sefin, under the pillars of organizational governance, in the face of the challenges faced to optimize organizational performance.